ANALISIS PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi Kasus Perusahaan Food and Beverage Yang Terdaftar di BEI Tahun 2017-2019) - Desti Wahyuningrum Ekawati; Afifudin Afifudin; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to determine the effect of institutional ownership, managerial ownership, independent commissioners and audit committee on company performance. The data used in this study are secondary data, the research population is Food and Beverage companies listed on the IDX while the research samples taken are Food and Beverage companies listed on the IDX in 2017-2019. The sampling technique was carried out using purposive sampling method. The results obtained by using multiple linear regression test Y = -0.266 + 0.005 X1 - 0.064 X2 + 0.955 X3 + 0.020 X4, and the test of this study using the t test. The results of this study indicate that partially institutional ownership has no effect on company performance, managerial ownership has no effect on company performance, independent commissioners have an effect on company performance and independent commissioners have no effect on the performance of Food and Beverage companies listed on the Indonesia Stock Exchange 2017-2019 period. Keywords: Institutional ownership, managerial ownership, independent commissioners and audit committee